Análise ergonômica da tarefa de abastecimento aeroviário do aeroporto Santos Dumont - Tavares, Helder de Souza (2007)
The workstation of Provisioning of Petrobrás in Santos Dumont airport is a work station that presents specific aspects while the maneuvers of work of your Operators of Provisioning (OP). Being a maintenance activity of one of the commercial flight services of the country (Rio - São Paulo), it deserves the attention there for the reliability of the works accomplished by the Operators of Provisioning (OP). The study was descriptive based on the physical ergonomics, in your aspect of evaluation of the risk of cumulative trauma disorders/work-related musculoskeletal disorder of the postures of the maneuvers of the tasks of provisioning/replenishment of OA in PAASD, where questionnaires and evaluations of the maneuvers of work in loco were accomplished. Methods of analysis were used (REBA) and of modeling biomechanics of the work maneuvers, as well as questionnaires of rising of risk of the task and of perception of muscular discomfort. The main objective was it of investigating the risks of cumulative trauma disorders/work-related musculoskeletal disorder through an ergonomic analysis of the postures of the maneuvers of the work tasks. The ergonomic study of the postures of the maneuvers could appear for fourteen work maneuvers, where eight of them were classified as of high risk and very loud